Estimating the impact of an integrated CCTV program on crime - Circo, Giovanni (Journal of experimental criminology, 2021)
Objectives Prior research has identified that CCTV cameras play some role in deterring crime in public places. However, increasingly, CCTV surveillance is being integrated with proactive monitoring and police response. This study uses a quasi-experimental design to determine the impact of an integrated CCTV program on crime in Detroit. Methods Data on the first 87 businesses in Project Green Light Detroit was collected, along with a matched comparison group of 201 other businesses. A Bayesian hierarchical linear growth curve model was employed to determine the effect of CCTV camera surveillance at Green Light businesses over the course of 2 years. Results Findings indicated that Green Light businesses experienced an immediate, but transient increase in property crime reports, as well as more consistent proactive police activity post-intervention. Over time, property crimes and disorder crimes decreased faster relative to the matched controls. There was little evidence of any impact on violent crimes. Conclusions Integrated CCTV programs may increase the reporting of minor crimes which may have not been reported before. However, these programs may not likely impact violent crimes. In addition, tying proactive response and patrol to participating businesses places higher manpower costs on departments. This has implications to other cities considering implementing wide-spread integrated CCTV programs like Project Green Light Detroit.